ANALISIS MANAJEMEN STRATEGIS PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK - Zalfa Lutfia Ananda; Novian Ekawaty (Economicus, 2024)
Indonesian people have known and used herbal medicine since ancient times as a cultural heritage. PT Industri Jamu Dan Farmasi Sido Muncul Tbk (SIDO) is a pharmaceutical company that produces herbal medicines, food and beverages, and pharmaceutical products, focusing on innovation and quality. This research aims to analyze the advantages, weaknesses, opportunities, and threats of PT Sido Muncul in the areas of marketing, finance, production, and human resources using descriptive qualitative methods with secondary data from financial statements. The results showed that by 2023, PT Sido Muncul's net sales decreased by 7.77% to Rp. 3.56 trillion and gross profit decreased by 12.95% to Rp. 2.08 trillion, due to the El-Nino phenomenon. The conclusion confirms Sido Muncul's commitment to quality human resource management and product innovation to sustain growth.